Global warming weakening the inherent stability of glaciers and permafrost - Ding, Yongjian; Zhang, Shiqiang; Zhao, Lin; Li, Zhongqin; Kang, Shichang (Science bulletin, 2019)
The Cryosphere has been undergoing a worldwide retreat, as seen in the decrease in the areal extent and volume of glaciers and in the areal extent of permafrost. This paper presents a systematic examination of the inherent stability changes of glaciers and permafrost caused by warming. Various study results suggest that over the past 30 years, the internal temperature of glaciers and permafrost exhibits an overall accelerating warming trend. The warming rate peaked in the mid-2000s and slowed slightly for several years afterward. In recent years, however, the warming rate has seemed to pick up again. The warming of glaciers and permafrost has exerted great impact on their stability, displayed as intensified melting, increased glacier surging, enlargement of supraglacial lakes, and increased permafrost degradation. Even without a future temperature increase, some glaciers will continue to shrink, and the number of surging glaciers will increase. The transition from low-temperature to high-temperature permafrost is a noticeable warning sign of a comprehensive degradation of permafrost. These results indicate that “warming” glaciers and permafrost will exert significant impacts on the hydrology, ecology, and stability of engineering in cold regions.